Dehydrogenation of ammonia for electricity production: Effect of recirculation fraction. Issue 6 (March 2021) - Juangsa, F B; Darmanto, P S; Aziz, M
Abstract: Hydrogen (H2) has been widely studied as a promising energy carrier. However, H2 has a challenging technology in the storage and transportation. Since, it is a critical technology for H2 energy system implementation, the H2 storage and transportation is remain to be solved. This work proposes an integrated system of energy utilization of ammonia (NH3), which has been known as one of the promising methods of H2 storage. The system includes the decomposition of ammonia (NH3) through thermo-catalytic process and also power generation process using H2 as fuel. The heat generated from oxy-fuel combustion of H2 is utilized to supply the thermal energy required for the endothermic process of NH3 decomposition, and the remaining heat is converted to electricity by a combined cycle. A portion of exhaust gas is recirculated to the combustion chamber, and the heat circulation of the system is designed and optimized based on enhanced process integration (EPI), resulting in a highly efficient system. The result shows an optimum configuration of the integrated system with a recirculation fraction of 0.5-0.55, which is resulting in high system efficiency of 51.4%. The proposed work demonstrated an integrated system of H2-based energy utilization of NH3 with CO2-free while maintaining a highly efficient system.